2018
DOI: 10.1103/physreve.98.012906
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of a rod penetrating into granular media

Abstract: We investigate experimentally the possible buckling of a thin rod when penetrating downwards into a granular packing. When its bottom end reaches a specific depth, the rod may start buckling provided that the embrace is not enough to stop that phenomenon. The critical rod depth z_{c} at buckling is observed to scale with the rod length L either as 1/L or 1/L^{2}. These two scalings are shown to arise from the two resistant force terms that come into play during the rod penetration: a pressure force at the bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…These values lay in the same range as previous estimations for flat-ended rods penetrating into glass beads [6]. Due to the finite size effect of the container, possible wall effect generated by friction may be expected [28][29][30].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These values lay in the same range as previous estimations for flat-ended rods penetrating into glass beads [6]. Due to the finite size effect of the container, possible wall effect generated by friction may be expected [28][29][30].…”
Section: Resultssupporting
confidence: 86%
“…In this study, we consider as a reference case the intrusion of the rod at a constant and low velocity without cycles. A previous study has shown that this force results from two contributions: the hydrostatic-like pressure applying on the tip of the rod and the frictional force exerting along its length [6]. They provided the following expression for the vertical force F 0 experienced during a continuous intrusion:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Such systems form periodically ordered liquid film architectures into which an elastic ribbon can be introduced. Although the question of complex deformation of an intruder in an architected medium has been widely studied in the case of granular media 15,16 with applications in the context of root growth, 17 a limited number of studies on model systems exist in the case of liquid foams, such as the analysis of simple arrangements of soap films interacting with rigid solids, 18 and simulations of flexible fibres in foam under shear. 19 We consider a model system composed of an ordered assembly of monodisperse soap bubbles and an elastomer ribbon (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems form periodically ordered liquid film architectures into which an elastic ribbon can be introduced. Although the question of complex deformation of an intruder in an architected medium has been widely studied in the case of granular media [15,16] with applications in the context of root growth [17], a limited number of studies on model systems exist in the case of liquid foams, such as the analysis of simple arrangements of soap films interacting with rigid solids [18], and simulations of flexible fibres in foam under shear [19]. We consider a model system composed of an ordered assembly of monodisperse soap bubbles and an elastomer ribbon (Fig.…”
Section: Introductionmentioning
confidence: 99%